Interaction of thymic stromal lymphopoietin, IL‐33, and their receptors in epithelial cells in eosinophilic chronic rhinosinusitis with nasal polyps - Liao, B.; Cao, P.‐P.; Zeng, M.; Zhen, Z.; Wang, H.; Zhang, Y.‐N.; Hu, C.‐Y.; Ma, J.; Li, Z.‐Y.; Song, J.; Liu, J.‐X.; Peng, L.‐Y.; et al. (Allergy (Copenhagen), 2015)
Background Thymic stromal lymphopoietin (TSLP), IL‐25, and IL‐33 system contribute to the initiation and development of Th2 responses. This study aimed to explore the involvement of TSLP, IL‐25, IL‐33, and their receptors in type 2 T‐helper (Th) responses in chronic rhinosinusitis with nasal polyps (CRSwNPs) and their cross‐regulation in human nasal epithelial cells (HNECs). Methods Immunohistochemistry, quantitative RT‐PCR, ELISA, Bio‐Plex assay, and flow cytometry were used to detect the expression of TSLP/common γ‐like TSLP receptor (TSLPR)/IL‐7 receptor α (IL‐7Rα), IL‐25/IL‐17B receptor (IL‐17RB), and IL‐33/membrane‐bound ST2 (ST2L)/soluble ST2 (sST2) in sinonasal mucosa and HNECs. HNECs cultured at an air–liquid interface were used to explore the expression in regulation of these cytokine systems. Results Compared with controls and noneosinophilic CRSwNP, the expression of TSLP/TSLPR/IL‐7Rα and ST2L/sST2 was significantly increased in eosinophilic CRSwNP, predominantly in epithelial cells. In contrast, the expression of IL‐33 and IL‐25/IL‐17RB was enhanced in epithelial cells in both eosinophilic and noneosinophilic CRSwNP compared to controls. The expression of TSLP, TSLPR, and ST2L was positively correlated with symptom and computer tomography scan scores in eosinophilic CRSwNP and with Th2 cytokine expression in sinonasal mucosa. The expression of ST2L was correlated with TSLP and its receptor expression. TSLP could induce ST2L expression that promoted IL‐33‐induced TSLP expression in HNECs. In addition, TSLP/TSLPR/IL‐7Rα and ST2L could be induced by Th2 cytokines, while IL‐25/IL‐17RB and IL‐33 could be upregulated by Th1/Th17 cytokines, in HNECs. Conclusions The positive feedback loop between TSLP, IL‐33 and their receptors, and Th2 cytokines may facilitate Th2‐skewed inflammation in eosinophilic CRSwNP.